The Effectiveness of Health Education Using Falshback and Video Methods on Balanced Nutrition Knowledge Among Children in Elementary School - Pratiwi, Dhini; Masluroh, Masluroh (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims:  This study aims to assess the efficacy of nutrition education using flipcharts and movies in enhancing the knowledge of Balanced Nutrition among elementary school students at SDN 1 Bina Karya Jaya, Putra Rumbia District, Central Lampung Regency in 2023. Method: The study used the Pretest-Posttest Control Group Design methodology to investigate 44 students at SDN 1 Bina Karya Jaya in Putra Rumbia, Central Lampung Regency. Result: The results showed that there were differences in the effectiveness of health education flipcharts and video methods on knowledge of balanced nutrition in students at SDN 1 Bina Karya Jaya, Putra Rumbia District, Central Lampung with a p-value of 0.000. Conclusion: To enable teaching staff to collaborate closely with health workers in order to provide frequent health education on proper nutrition for school-age children, therefore preventing nutritional issues in children.